Repeat‐Associated Non‐AUG Translation of AGAGGG Repeats that Cause X‐Linked Dystonia‐Parkinsonism. Issue 11 (16th August 2022) - Reyes, Charles Jourdan; Asano, Katsura; Todd, Peter K.; Klein, Christine; Rakovic, Aleksandar
Abstract: Background: X‐linked dystonia‐parkinsonism (XDP) is a neurodegenerative disorder caused by the intronic insertion of a SINE‐VNTR‐ Alu (SVA) retrotransposon carrying an (AGAGGG) n repeat expansion in the TAF1 gene. The molecular mechanisms by which this mutation causes neurodegeneration remain elusive. Objectives: We investigated whether (AGAGGG) n repeats undergo repeat‐associated non‐AUG (RAN) translation, a pathogenic mechanism common among repeat expansion diseases. Methods: XDP‐specific RAN translation reporter plasmids were generated, transfected in HEK293 cells, and putative dipeptide repeat proteins (DPRs) were detected by Western blotting. Immunocytochemistry was performed in COS‐7 cells to determine the subcellular localization of one DPR. Results: We detected putative DPRs from two reading frames, supporting the translation of poly‐(Glu‐Gly) and poly‐(Arg‐Glu) species. XDP RAN translation initiates within the (AGAGGG) n sequence and poly‐(Glu‐Gly) DPRs formed nuclear inclusions in transfected cells. Conclusions: In summary, our work provides the first in‐vitro proof of principle that the XDP‐linked (AGAGGG) n repeat expansions can undergo RAN translation. © 2022 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society